2016
DOI: 10.1186/s40689-016-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Scope of using jute fiber for the reinforcement of concrete material

Abstract: The natural jute fiber can be the effective material to reinforce concrete strength which will not only explore a way to improve the properties of concrete, it will also explore the use of jute and restrict the utilization of polymer which is environmentally detrimental. In Bangladesh, jute is locally available and, hence, less expensive. To achieve this goal, an experimental investigation of the compressive, flexural, and tensile strengths of Jute Fiber Reinforced Concrete Composites (JFRCC) has been conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 13 publications
(20 reference statements)
10
40
1
Order By: Relevance
“…e outcome suggested that the strength was enhanced while utilizing jute fiber up to 0.50% as reinforcement components and with further addition of jute fiber in concrete; the strength reduces due to the maximum number of voids generated by jute fiber addition which is greater than the optimum level of voids produced in concrete. is trend was observed by Zarakia et al [40]. Islam and Ahmed [18] stated that the compressive strength was reduced while utilizing jute fiber beyond 0.50% as the reinforcement ingredient in concrete.…”
Section: Compressivementioning
confidence: 58%
“…e outcome suggested that the strength was enhanced while utilizing jute fiber up to 0.50% as reinforcement components and with further addition of jute fiber in concrete; the strength reduces due to the maximum number of voids generated by jute fiber addition which is greater than the optimum level of voids produced in concrete. is trend was observed by Zarakia et al [40]. Islam and Ahmed [18] stated that the compressive strength was reduced while utilizing jute fiber beyond 0.50% as the reinforcement ingredient in concrete.…”
Section: Compressivementioning
confidence: 58%
“…The variation with in the various percentage of addition fibers tends that at 0.6 percentage addition fibers has higher strength than the other two percentage of addition of fibers. The decrease in the strength initiates from 0.7 % this may be due to fiber agglomeration [27]. The percentage variation in the compressive strength of concrete are shown in figure 4.…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…The slabs were taken out from the controlled environment after 24 h. (Figure 4). Darjole et al [17] reported that enhancement in compressive strength ranged from 3.25% to 21.4% due to combination of Steel and polypropylene fibers to the concrete. As a result, using 15 mm length of JFRC with ≤0.30 % fiber addition culminates to more pledging combination for compressive strength enhancement.…”
Section: Plastic Shrinkage Testingmentioning
confidence: 99%
“…The main defects associated with the use of synthetic fibers are relatively high cost and health and environmental imperilment. On the other hand, natural fibers which are biodegradable, cheap, environmentally friendly, and easily available as reported by Zakaria et al (2016) are cultivated from naturally available resources, for example, coconut tree, banana tree, cotton, and jute. Therefore, making good-quality and low-cost sustainable FRC for housing the requirements to employ natural fibers are expanding.…”
Section: Introductionmentioning
confidence: 99%